Metabolomics Applied to Pediatric Asthma: What Have We Learnt in the Past 10 Years? - Valentina Agnese Ferraro; Stefania Zanconato; Silvia Carraro (MDPI AG, 2023)
Background: Asthma is the most common chronic condition in children. It is a complex non-communicable disease resulting from the interaction of genetic and environmental factors and characterized by heterogeneous underlying molecular mechanisms. Metabolomics, as with the other omic sciences, thanks to the joint use of high-throughput technologies and sophisticated multivariate statistical methods, provides an unbiased approach to study the biochemical-metabolic processes underlying asthma. The aim of this narrative review is the analysis of the metabolomic studies in pediatric asthma published in the past 10 years, focusing on the prediction of asthma development, endotype characterization and pharmaco-metabolomics. Methods: A total of 43 relevant published studies were identified searching the MEDLINE/Pubmed database, using the following terms: "asthma" AND "metabolomics". The following filters were applied: language (English), age of study subjects (0-18 years), and publication date (last 10 years). Results and Conclusions: Several studies were identified within the three areas of interest described in the aim, and some of them likely have the potential to influence our clinical approach in the future. Nonetheless, further studies are needed to validate the findings and to assess the role of the proposed biomarkers as possible diagnostic or prognostic tools to be used in clinical practice.